Sleep pressure accumulates in a voltage-gated lipid peroxidation memory - H. Olof Rorsman; Max A. Müller; Patrick Z. Liu; Laura Garmendia Sanchez; Anissa Kempf; Stefanie Gerbig; Bernhard Spengler; Gero Miesenböck (Nature, 2025)
Abstract Voltage-gated potassium (K V ) channels contain cytoplasmically exposed β-subunits 1–5 whose aldo-keto reductase activity 6–8 is required for the homeostatic regulation of sleep 9 . Here we show that Hyperkinetic, the β-subunit of the K V 1 channel Shaker in Drosophila 7 , forms a dynamic lipid peroxidation memory. Information is stored in the oxidation state of Hyperkinetic’s nicotinamide adenine dinucleotide phosphate (NADPH) cofactor, which changes when lipid-derived carbonyls 10–13 , such as 4-oxo-2-nonenal or an endogenous analogue generated by illuminating a membrane-bound photosensitizer 9,14 , abstract an electron pair. NADP + remains locked in the active site of K V β until membrane depolarization permits its release and replacement with NADPH. Sleep-inducing neurons 15–17 use this voltage-gated oxidoreductase cycle to encode their recent lipid peroxidation history in the collective binary states of their K V β subunits; this biochemical memory influences—and is erased by—spike discharges driving sleep. The presence of a lipid peroxidation sensor at the core of homeostatic sleep control 16,17 suggests that sleep protects neuronal membranes against oxidative damage. Indeed, brain phospholipids are depleted of vulnerable polyunsaturated fatty acyl chains after enforced waking, and slowing the removal of their carbonylic breakdown products increases the demand for sleep.